Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1136/practneurol-2020-002557
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of acute ischaemic stroke

Abstract: Acute ischaemic stroke is a major public health priority and will become increasingly relevant to neurologists of the future. The cornerstone of effective stroke care continues to be timely reperfusion treatment. This requires early recognition of symptoms by the public and first responders, triage to an appropriate stroke centre and efficient assessment and investigation by the attending stroke team. The aim of treatment is to achieve recanalisation and reperfusion of the ischaemic penumbra with intravenous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 116 publications
(90 reference statements)
0
59
0
10
Order By: Relevance
“…The approach to an efficient and focused history and physical examination in suspected acute stroke has been outlined in the first article in this series. 10 It is important to obtain a history of any recent trauma, including from a witness if available, and to assess for any circumstantial evidence, making sure to determine clinically whether the trauma preceded the haemorrhage or vice versa. Acute ischaemic stroke and ICH cannot be reliably distinguished at the bedside but the diagnosis is made rapidly and easily on imaging, so every effort should be made to minimise delays to the initial CT brain scan.…”
Section: Acute Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to an efficient and focused history and physical examination in suspected acute stroke has been outlined in the first article in this series. 10 It is important to obtain a history of any recent trauma, including from a witness if available, and to assess for any circumstantial evidence, making sure to determine clinically whether the trauma preceded the haemorrhage or vice versa. Acute ischaemic stroke and ICH cannot be reliably distinguished at the bedside but the diagnosis is made rapidly and easily on imaging, so every effort should be made to minimise delays to the initial CT brain scan.…”
Section: Acute Evaluationmentioning
confidence: 99%
“… 45 The general principles of acute care are the same as those for acute ischaemic stroke, as outlined in the first article in this series. 10 Secondary prevention measures, cerebral small vessel disease and decisions regarding restarting antithrombotic therapy will be addressed in subsequent articles.…”
Section: Acute Managementmentioning
confidence: 99%
“…Imaging modalities, such as advanced MRI and CT medical imaging, have been shown to be critical in improving clinical stroke care in clinical practice. For example, Hurford et al 14 reported on AIS management using a CT imaging workflow. Currently used imaging techniques include non-contrast CT (NCCT), CTA, CT perfusion (CTP) and MRI.…”
Section: Introductionmentioning
confidence: 99%
“…4 The etiology of a stroke correlates with its neuroanatomical location in the brain, clinical presentation, and appropriate treatment. 5 Appropriate treatment of stroke is a matter of extreme urgency because neurons die rapidly, within minutes of losing their blood supply. New treatments such as endovascular thrombectomy have significantly improved the outcomes of some types of stroke.…”
mentioning
confidence: 99%
“…New treatments such as endovascular thrombectomy have significantly improved the outcomes of some types of stroke. 5 Research into new stroke etiologies and treatments would benefit from precise data on the neuroanatomical location of strokes in the brain. Textbooks and review articles about stroke have abundant information on the epidemiology, risk factors, pathophysiology, and many clinical features, but lack specific numerical quantitation on the neuroanatomical distribution of strokes.…”
mentioning
confidence: 99%